WIC Is Critical During the COVID-19 Pandemic: Lessons Learned From Los Angeles County Participants. (7th June 2021) - Au, Lauren; Ritchie, Lorrene; Vital, Nicole; Tsai, Marisa; Anderson, Christopher; Meza, Martha; Martinez, Catherine; Whaley, Shannon
Abstract: Objectives: The COVID-19 pandemic has changed the way that the Special Supplemental Nutrition Program for Women, Infants and Children (WIC) delivers services. The USDA granted multiple waivers to allow flexibility in WIC operations during the pandemic. The objective of this study was to hear from WIC participants about the impact of changes due to COVID-19. Methods: In the summer of 2020, 60 semi-structured interviews were completed, half with English-speaking and half with Spanish-speaking WIC participants in the Los Angeles area. Interviews were recorded, transcribed, and analyzed using a deductive content analysis approach to describe responses and identify themes. Results: Four themes emerged: 1 ) The pandemic has exacerbated the ckhallenges facing low-income families; 2 ) WIC continues to be a valued resource especially under the challenging circumstances; 3 ) WIC's transition to remote service delivery has ensured that families continue to receive not only critical WIC food benefits, but also nutrition education and support; 4 ) Lessons learned during COVID-19 can inform needed WIC modernizations to maximize WIC's proven benefits post-pandemic. Nearly 75% of WIC participants faced reductions in income due to job loss or reduced work hours. Nearly 60% of households reported experiencing food insecurity. Early in the pandemic, many reported challenges accessing WIC-eligible foods, resulting in lost food benefits. Approximately 43% reported getting food from a food pantry or church, with most (77%) reporting first time usage. Participants shared that even with the change to only remote education, they valued the information and were very satisfied with WIC services. The majority (83%) found the California WIC App helpful in informing what WIC foods they could purchase. Participants also reported that enrolling in WIC remotely was easier than coming in-person and they were comfortable providing documents related to income and eligibility determination remotely. Conclusions: WIC has been essential in helping families cope with COVID. WIC's transition to remote service delivery has ensured seamless and safe delivery of services, helping families with young children during an unprecedented time of need. Funding Sources: The David and Lucile Packard Foundation